PENEGAKAN HUKUM DAERAH ALIRAN SUNGAI CITARUM, SOLUSI PRAKTIS MENUJU KELESTARIAN LINGKUNGAN - R. Jossi Sutari Belgradoputra; Irma Verlianara; T. Banjarnahor (PRANATA HUKUM, 2022)
In 358 - 382 AD, a Maharesi or Pastor from Salankayana, India named Jayashingawarman built a small hamlet on the banks of a river around which many Tarum (Indigofera) trees grow, which is a type of blue-producing plants. Gradually the hamlet developed into a large kingdom, namely the Tarumanegara Kingdom. The river is the Citarum river. The Citarum River is the longest river in West Java which flows approximately 297 kilometers, sourced from the Mount Wayang springs (south of Bandung City), then flows north through the Bandung Basin and empties into the Java Sea, Karawang district. Citarum is one of the most important watersheds in West Java Province, which makes a major contribution to the lives of the surrounding communities, both for clean water needs, water supply for agricultural, industrial, and other purposes. The surrounding population uses fishery resources in this river, either traditionally by fishing or fishing. However, in the last 30 years, environmental deforestation, pollution of household waste, factory waste to sedimentation and erosion have become problems that have undermined water quality and flow coverage.Environmental preservation is very necessary for all of us, so that our future generations can still enjoy sustainable living resources.